2013
DOI: 10.1523/jneurosci.3978-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

The Adhesion-GPCR BAI1 Regulates Synaptogenesis by Controlling the Recruitment of the Par3/Tiam1 Polarity Complex to Synaptic Sites

Abstract: Excitatory synapses are polarized structures that primarily reside on dendritic spines in the brain. The small GTPase Rac1 regulates the development and plasticity of synapses and spines by modulating actin dynamics. By restricting the Rac1-guanine nucleotide exchange factor Tiam1 to spines, the polarity protein Par3 promotes synapse development by spatially controlling Rac1 activation. However, the mechanism for recruiting Par3 to spines is unknown. Here, we identify brain-specific angiogenesis inhibitor 1 (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
149
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(157 citation statements)
references
References 57 publications
8
149
0
Order By: Relevance
“…Synaptic plasticity can be associated with changes in dendritic spine morphology (26). A recent in vitro study suggested that BAI1 interaction with the PAR3/TIAM1 polarity complex regulates spinogenesis in neurons in culture (10). Therefore, we examined whether the aberrant synaptic plasticity in Bai1 -/-mice correlated with alterations in dendritic spine morphology in ex vivo Bai1 -/-hippocampus.…”
Section: Generation and Characterization Of Bai1mentioning
confidence: 98%
See 1 more Smart Citation
“…Synaptic plasticity can be associated with changes in dendritic spine morphology (26). A recent in vitro study suggested that BAI1 interaction with the PAR3/TIAM1 polarity complex regulates spinogenesis in neurons in culture (10). Therefore, we examined whether the aberrant synaptic plasticity in Bai1 -/-mice correlated with alterations in dendritic spine morphology in ex vivo Bai1 -/-hippocampus.…”
Section: Generation and Characterization Of Bai1mentioning
confidence: 98%
“…Brain-specific angiogenesis inhibitor 1 (BAI1) was recently identified as a postsynaptic density (PSD) protein (9,10). BAI1 is a member of the adhesion GPCR subfamily (11), initially identified in a screen for p53-regulated genes (12).…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion GPCRs are a growing research field, and several of these receptors have shown an important role in the CNS (Araç et al, 2012a; Langenhan et al, 2013;Strokes and Piao, 2010). For example, the brain-specific angiogenesis inhibitor (BAI) subfamily is involved in the control of synaptogenesis (Duman et al, 2013;Stephenson et al, 2014), whereas the latrophilins have been implicated in the control of synaptic transmission (O'Sullivan et al, 2012;O'Sullivan et al, 2014) and GPR56 is associated with brain development (Jeong et al, 2012;Luo et al, 2011;Singer et al, 2013).…”
Section: Abstract: Neuron Gpcr Nerve Net Synapse Evolutionmentioning
confidence: 99%
“…The brain-specific angiogenesis inhibitor family (BAIs; subfamily VII adhesion GPCRs) members are well characterised for their roles in synaptogenesis, involving regulation of synapses and synaptic density (for a review, see Stephenson et al, 2014). Recently, Duman and colleagues provided evidence that BAI1 can regulate synaptogenesis by coupling with Rac1, mediated by a specific interaction and recruitment of the Par3/Tiam1 polarity proteins to postsynaptic sites (Duman et al, 2013). Also, the C-terminal region of BAI1 interacts with PDZ-domain-containing proteins, including MAGI-2 and MAGI-3 (Stephenson et al, 2013).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation